2012
DOI: 10.1080/10810730.2011.635769
|View full text |Cite
|
Sign up to set email alerts
|

Improving Media Message Interpretation Processing Skills to Promote Healthy Decision Making About Substance Use: The Effects of the Middle School Media Ready Curriculum

Abstract: The Media Ready Program was designed as a middle school, media literacy education, preventive intervention program to improve adolescents' media literacy skills and reduce their intention to use alcohol or tobacco products. In a short-term efficacy trial, schools in North Carolina were randomly assigned to conditions (Media Ready: n = 214; control: n = 198). Boys in the Media Ready group reported significantly less intention to use alcohol in the future than did boys in the control group. Also, students in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
40
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(47 citation statements)
references
References 32 publications
4
40
0
Order By: Relevance
“…The program's positive impact on media deconstruction skills was consistent with two previous alcohol media literacy studies, which found that students had improved media deconstruction skills as a result of the intervention (Kupersmidt et al, 2010(Kupersmidt et al, , 2012. The current study further showed that results were maintained 3 months after the intervention.…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations
“…The program's positive impact on media deconstruction skills was consistent with two previous alcohol media literacy studies, which found that students had improved media deconstruction skills as a result of the intervention (Kupersmidt et al, 2010(Kupersmidt et al, , 2012. The current study further showed that results were maintained 3 months after the intervention.…”
Section: Discussionsupporting
confidence: 78%
“…The wait-list control group also showed decreased scores from Wave 2 to Wave 3, t(86) = 5.84, p < .001, 2 = .28, with these posttest decreases significantly lower than at Wave 1, t(80) = 4.45, p < .001, 2 = .20. Both groups again showed a significant effect of the intervention for decreasing (Kupersmidt et al, 2010(Kupersmidt et al, , 2012, measured students' ability to deconstruct alcohol advertisements. Students viewed an advertisement for the alcoholic beverage Midori and then responded to the following items: (1) What product is being sold in the ad?…”
Section: Analysesmentioning
confidence: 89%
See 2 more Smart Citations
“…Increasing media literacy may help young people critically assess advertising messages that portray alcohol in an overly positive light. For example, a preventive intervention program aimed at improving media literacy skills among middle school youths found significant reductions in intentions to use alcohol in the intervention condition relative to controls [83]. Previously, Chen [82] enrolled adolescents into the TeenSmart TV media literacy program that included a negative media lesson condition and a balanced evaluative approach condition.…”
Section: Intervention Strategiesmentioning
confidence: 99%